Pengaruh Workplace Well Being Terhadap Employee Performance Yang Dimediasi Oleh Employee Engagement pada CV Wira Jaya Abadi Denpasar - Ni Komang Vina Rahayu; Octavianus Sumardana Pratama; Putu Gede Denny Herlambang (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Employee performance is the result of work in terms of quality and quantity achieved by an employee in carrying out their duties in accordance with the responsibilities given to the employee. There is a phenomenon where some employees are deemed to have not achieved the expected performance standards. This research aims to determine and analyze the influence of workplace well-being on employee performance which is mediated by employee engagement at CV Wira Jaya Abadi Denpasar. The research population was 54 employees with the sampling technique used in this research was saturated sampling. The data analysis method uses multiple linear regression analysis and path analysis using classical assumption testing first. Overall, each hypothesis shows a positive and significant influence. Among them, workplace well being on employee engagement, employee engagement on employee performance, workplace well being on employee performance, and employee engagement play a role in mediating the influence of workplace well-being on employee performance.